Vertical FDI Revisited - Henrik Braconier; Pehr-Johan Norbäck; Dieter Urban (The Research Institute of Industrial Economics (IUI), 2002)
This study explores how relative skilled-wage premia affect FDI. Contrary to previous studies based on factor endowment differences, we find strong support for vertical FDI, in the sense that more FDI is conducted in countries where unskilled labor is relatively cheap. In addition, we find t hat relative skill-premia also affect FDI activities that have previously been associated with horizontal FDI, i.e. local affiliate sales. Consequently, the potential effects of changes in the relative wage costs on international production reallocation within MNEs are large. In fact, if not for the 8% rise in the US skilled wage premium relative to the average host country between 1986-1994, annual US affiliate sales abroad in relation to US GDP would have been half a percentage point higher.
Keywords: F13; F23; J31; 330; Multinational Firms; Skilled-Wage Premium; New Trade Theory; Direktinvestition; Arbeitskosten; Lohnstruktur; Qualifikation; Schweden; USA; Welt